Preparation and surface modification of hollow fibre membranes for drinking water disinfection and water reclamation. (13th September 2010) - Ray, P.; Singh, P.S.; Parashuram, K.; Maurya, S.R.; Trivedi, J.J.; Devmurari, C.V.; Rao, N.N.; Waghmare, S.; Reddy, A.V.R.
Polysulphone hollow fibres were spun according to phase inversion process under different conditions by extrusion of dimethylformamide solution of the polymer through double orifice spinneret using water or water-DMF mixture as gelation medium. The membrane surface was modified by in situ interfacial polymerisation of m-phenylenediamine with trimesoyl chloride. The nominal molecular weight cut-off (MWCO) values of the virgin fibres were 44, 000?94, 000 g/mol, which were decreased to 10, 000?14, 000 g/mol upon surface modification. The contact angle of the virgin fibres was about 87° and was decreased to about 65° by surface modification. HF modules exhibited pure water fluxes of 40?70 litre/m²h at 25 psi, and 4?5 log reduction for microorganisms like cocci, E. coli and bacillus when tested with water containing 1010 cfu/ml of bacteria. Fibres were tested for the treatment of municipal sewage water for a period of 20 days and constant rejection-flux profile was observed throughout the period.